2009
DOI: 10.1016/j.biomaterials.2008.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic nanofibrous gelatin/apatite composite scaffolds for bone tissue engineering

Abstract: Mimicking certain features (e.g. nanoscale topography and biological cues) of natural extracellular matrix (ECM) is advantageous for the successful regeneration of damaged tissue. In this study, nanofibrous gelatin/apatite (NF-gelatin/apatite) composite scaffolds have been fabricated to mimic both the physical architecture and chemical composition of natural bone ECM. A thermally induced phase separation (TIPS) technique was developed to prepare nanofibrous gelatin (NF-gelatin) matrix. The NF-gelatin matrix mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
327
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(334 citation statements)
references
References 29 publications
(25 reference statements)
5
327
1
1
Order By: Relevance
“…48 Originally, the technique was demonstrated with PLLA or PLGA, but more recently, the technique has been performed with polyhydroxyalkanoate, 49 chitosan, 47 gelatin, 50 and gelatin/apatite composites. 51 The advantages of this method are that it does not require specialized equipment, and there is little variation between batches. Additionally, constructs can be produced in a mold to achieve a specific geometry.…”
Section: Phase Separationmentioning
confidence: 99%
“…48 Originally, the technique was demonstrated with PLLA or PLGA, but more recently, the technique has been performed with polyhydroxyalkanoate, 49 chitosan, 47 gelatin, 50 and gelatin/apatite composites. 51 The advantages of this method are that it does not require specialized equipment, and there is little variation between batches. Additionally, constructs can be produced in a mold to achieve a specific geometry.…”
Section: Phase Separationmentioning
confidence: 99%
“…However, because bacterial cellulose is hydrogel-like, with a high water holding capacity, it may be possible to incorporate drugs and growth factors in the scaffold. In addition, the deposition of calcium phosphate mineral onto bacteria cellulose [31][32][33] may improve bone formation; model studies have shown that a hydroxyapatite layer increases the expression of mRNA encoding the bone matrix proteins osteocalcin, osteopontin, and bone sialoprotein [34,35].…”
Section: Cell Studymentioning
confidence: 99%
“…The need for bone substitutes to replace/restore the function of damaged/lost bone has become a major clinical challenge [1,2]. Current research, serious advances have been accomplished to treat the difficulty or displeasure of bone implant materials with cell/tissues based tissue engineering.…”
Section: Introductionmentioning
confidence: 99%